Epidemiology and national trends in prevalence and surgical management of metastatic spinal disease. (July 2018) - Horn, Samantha R.; Dhillon, Ekamjeet S.; Poorman, Gregory W.; Tishelman, Jared C.; Segreto, Frank A.; Bortz, Cole A.; Moon, John Y.; Behery, Omar; Shepard, Nicholas; Diebo, Bassel G.; Vira, Shaleen; Passias, Peter G.
Highlights: Increase in incidence of spinal metastasis diagnoses during the last decade. Increase in surgical treatment for spine metastasis during the last decade. Complication rates, in-hospital mortality, and length of stay remain stable. Abstract: Surgical treatment for spinal metastasis has benefited from improvements in surgical techniques. However, the trends in treatment and outcomes for spinal metastasis surgery have not been well-established in a pediatric population. Patients <20 years old with metastatic spinal tumors undergoing spinal surgery were identified in the KID database. Trends for spinal metastases treatment and patient outcomes were analyzed using weight-adjusted ANOVAs. 333 patients were identified in the KID database. The top five primary diagnoses were metastatic brain/spinal cord tumor (19.8%), metastatic nervous system tumor (15.9%), metastatic bone cancer (13.2%), spinal cord tumor (4.2%), and tumor of ventricles (3.0%). There was an increased incidence of spinal metastasis diagnoses from 2003 to 2012 (88.5–117.9 per 100, 000; p < 0.001) and an increased trend in the incidence of surgical treatment for spinal metastasis from 2003 to 2012 (p = 0.014). The average age was 10.19 ± 6.33 years old and 38.4% were female. The average length of stay was 17.34 ± 24.36 days. Average CCI increased over time (2003: 7.87 ± 1.40, 2012: 8.44 ± 1.39; p = 0.006). The most common surgeries were excision of spinal cord/meninges lesions (69.1%) and decompression of spinal canal (38.1%). Length of hospital stay and in-hospital mortality did not change over time (17.34–18.04 days, p = 0.337; 1.6%–2.9%, p = 0.801). 10.5% of patients underwent a posterior fusion and 22.2% had at least one complication (nervous system, respiratory, dysphagia, infection). The overall complication rate remained stable over time (23.4%–21.8%, p = 0.952). Surgical treatment for spinal metastasis in the last decade has increased, though the complication rates, in-hospital mortality, and length of stay have remained stable.